Preventing the Root Causes of Youth Homelessness Through Cultural and Critical Pedagogies: An Autoethnographic Qualitative Study of Quebec Schools and Institutions Informed by Lived and Professional Experience - Battista, Adriano (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
This article examines the role of schools in preventing youth homelessness through a qualitative autoethnographic study conducted in Quebec from 2022 to 2025. Drawing on over 150 pages of field notes and constructed vignettes, the research integrates the author’s lived experience of homelessness with professional practice as an educator in underfunded, multilingual school settings in Kanien’kehá:ka /Montreal. Using thematic analysis, the study reveals how systemic exclusion, invisibility, and trauma shape the educational experiences of precariously housed youth. Schools are shown to be both sites of harm and potential, where individual care often collides with institutional constraint. By mobilizing cultural and critical pedagogies, the study argues that schools, if properly equipped, can act as upstream prevention spaces. Methodologically, the article demonstrates the value of autoethnography for uncovering insights into youth homelessness often missed by detached, statistical research. This work offers actionable recommendations for teacher training, education policy, and community-engaged research, advancing a relational, justice-centered approach to homelessness prevention in Quebec and beyond.